Dividend taxation, share repurchases and the equity trap - Tobias Lindhe; Jan Södersten (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper reconsiders the effects of dividend taxation. Particular attention is paid to the form of the equity trap, that is, the extent to which cash paid to the shareholders must be taxed as dividends. Our analysis shows that Sinn's (1991) criticism of the well-known King and Fullerton (1984) methodology for underestimating the cost of new share issues amounts to a misleading comparison across two different regimes for the equity trap. Contrary to Sinn, we find that when dividends are paid following a new issue, as assumed by King-Fullerton, the cost of capital is higher than is the case when no dividends are paid.
Keywords: H24; H25; H32; 330; dividend taxation; share repurchases; equity trap; cost of capital; nucleus theory; growth path; Kapitalertragsteuer; Aktienrückkauf; Kapitalkosten; Unternehmenswachstum; Theorie